The impact of clothing and protective gear on biophysical, physiological, perceptual and performance responses of rugby players during a simulated rugby protocol - Cannon, Michael-John (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2012)
Background: Clothing and protective gear worn during intermittent exercise has shown to increase physiological and perceptual responses, and negatively impact performance capacities, due to increased heat strain, suggested to hasten the onset of fatigue. However, the mechanisms of fatigue experienced in rugby remain unclear. Objectives: The aim of this study was establish whether clothing and protective gear worn during a simulated rugby protocol impacts players' biophysical, physiological, perceptual and performance responses. Methods: 15 registered university and school first XV rugby players with a mean (± SD) age of 20.9 years (± 1.9) volunteered to participate in the study. Testing was performed in a controlled laboratory setting, with temperatures having to be within the range of 16º C-22º C. The mean (± SD) ambient temperature was 17.6º C (± 1.6) for the control condition and 17.3º C (1.5) for the experimental condition. The mean (± SD) relative humidity was 65.2 % (± 9.5) for the control condition and 66.3 % (± 10.0) for the experimental condition. Player's performed two protocols of 80-minutes; a control condition (minimal clothing and protective gear) and an experimental condition (full clothing and protective gear). Physiological, perceptual and performance responses were measured at set intervals during the protocol, while biophysical responses were measured pre-, at half-time and post-protocol during a 3-minute EMG treadmill protocol. Results: Muscle activity significantly (p< 0.05) increased with increasing running speeds. There were no significant (p> 0.05) differences for muscle activity between conditions, except for the semitendinosus muscle, which was significantly (p< 0.05) higher during the control condition while running at high speeds. Players' heart rates, core temperatures and perceptual responses were significantly (p< 0.05) higher during the experimental condition, compared to the control condition. Performance responses were significantly (p< 0.05) lower during the experimental condition. Conclusion: The main driver of physiological and perceptual responses was the exercise itself. However, the additional clothing and protective gear exacerbated the responses, particularly towards the end stages of the protocol. This negatively impacted players' performance. Muscle activity appeared to be unaffected by increased body temperatures. However, core temperatures never reached critically high levels during either condition.
Keywords: Protective clothing -- Rugby football -- Health aspects -- Research; Rugby football injuries -- Prevention -- Research; Sports injuries -- Prevention -- Research